Clearinghouse access and bank runs: comparing New York and Chicago during the Panic of 1907 - Jon R. Moen; Ellis W. Tallman (Federal Reserve Bank of Atlanta, 1995)
During the Panic of 1907, New York City trust companies were not members of the New York Clearinghouse whereas trust companies in Chicago were members of the Chicago Clearinghouse. We argue that the apparent isolation of New York City trust companies from the pool of bank reserves controlled by the New York Clearinghouse led to the large-scale depositor runs on the New York City trusts. In contrast, Chicago trust companies had direct access to the Chicago Clearinghouse and their pool of reserves and did not suffer large-scale depositor withdrawals. Statistical evidence on a cross-section of intermediaries in both New York and Chicago supports this contention.
Keywords: 330; Bank failures; Banks and banking - History; Clearinghouses (Banking); Chicago (Ill.); New York (N.Y.)